An Instrument-Free Demonstration of Quantum Key Distribution for High-School Students - Sepulveda-Salas, J; Hernandez-Silva, C; Herrera-Urbina, F; Tecpan-Flores, S (Institute of Physics Publishing, 2019)
It has become increasingly common for high-school students to see media reports on the importance of quantum mechanics in the development of next-generation industries such as drug development and secure communication, but few of them have been exposed to fundamental quantum mechanical concepts in a meaningful classroom activity. In order to bridge this gap, we design and implement a low-cost 20 min demonstration of the Bell test, which is used in several entanglement-based quantum key distribution protocols. The demonstration introduces ideas such as the quantum state, quantum measurement, spin quantization, cryptography, and entanglement; all without using concepts beyond the 9th grade of the Chilean high-school curriculum. The demonstration can serve to promote early exposure of the future adopters and developers of quantum technology with its conceptual building blocks, and also to educate the general public about the importance of quantum mechanics in modern industry. © 2019 IOP Publishing Ltd.